2021
DOI: 10.1177/21676968211042109
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Life Satisfaction and Mental Health in Emerging Adulthood During the COVID-19 Pandemic. Risk and Protective Factors

Abstract: The COVID-19 pandemic has disrupted emerging adults’ daily routines due to social distancing, stay-at-home orders, and public and educational facilities’ closure. This article uses longitudinal panel data from Germany ( N = 625) to explore how the COVID-19 pandemic affects emerging adults’ mental health and life satisfaction. Specifically, we investigate risk and protective factors for within-person changes in life satisfaction and mental health using change score models. Our analysis reveals three main findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 90 publications
6
38
0
Order By: Relevance
“…Due to young adults being at a critical point in their careers, social life, and education, COVID-19 related disruptions may be particularly damaging to their mental health and wellbeing (Preetz et al, 2021;Stroud and Gutman, 2021). In addition, previous research has emphasised that young adults, who may have less experience of previous life disruptions and adaptation processes, are particularly vulnerable in times of crises (Weinberger et al, 2018).…”
Section: Figure 12 Mental Health/wellbeing Affected By the Covid-19 P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to young adults being at a critical point in their careers, social life, and education, COVID-19 related disruptions may be particularly damaging to their mental health and wellbeing (Preetz et al, 2021;Stroud and Gutman, 2021). In addition, previous research has emphasised that young adults, who may have less experience of previous life disruptions and adaptation processes, are particularly vulnerable in times of crises (Weinberger et al, 2018).…”
Section: Figure 12 Mental Health/wellbeing Affected By the Covid-19 P...mentioning
confidence: 99%
“…Section 1.2.4 provided an overview of Irish data (from the CSO and Healthy Ireland) showing widespread declines in mental health and wellbeing over the course of the pandemic, with young people experiencing both higher rates of mental ill-health prior to the pandemic, and greater declines during the pandemic. In terms of risk and protective factors for mental health and wellbeing decline during the pandemic, a number of direct and indirect mechanisms have been identified (Chandola et al, 2020;Gruber et al, 2021;Hu and Qian, 2021;Le and Nguyen, 2021;Preetz et al, 2021;Serrano-Alercon et al, 2021). The pandemic may have a direct effect on mental health and wellbeing via increased fear, anxiety and stress about one's own and family members' risk of infection, illness or hospitalisation due to the virus (Le and Nguyen, 2021).…”
Section: Mental Health and Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, the mental health and life satisfaction has declined among emerging adults, especially among those experiencing limited peer interactions and constraints in finances ( Egcas et al, 2021 ; Preetz, et al, 2021 ). Recent research among Filipino emerging adults have demonstrated how the societal impacts of the pandemic had greatly impacted the achievement of their developmental milestones, such as finishing college and entering the workforce ( Cleofas, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus crisis has introduced many challenges in the lives of emerging adults. Studies have indicated that emerging adults experienced disruptions of routines, lack of social contact, financial strain, family-related stress, unhealthy behaviors, school- and work-related stress, emotional distancing, fear of infection, negative perceptions of the future, and overall decreased quality of life during the COVID-19 outbreak ( Bianchi et al., 2021 ; Dotson et al., 2022 ; Hall & Zygmunt, 2021 ; Halliburton et al, 2021 ; Preetz et al, 2021 ). The Philippines, a country that belongs to the list with the longest lockdown and poorest COVID resilience scores ( Chang et al, 2022 ), also present similar problems, especially in the college population ( Cleofas, 2021a , 2021b ; Egcas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%